The Evolution of Political Narratives in the Digital Age in the United States of America - Katula, Richard A. (Horyzonty Wychowania, 2018)
RESEARCH OBJECTIVE: The objective of this essay is to demonstrate how political narratives in the United States of America, specifically, Presidential campaign advertisements, have addressed the problem of audience. THE RESEARCH PROBLEM AND METHODS: Through historical and critical analysis/research the essay traces the concept of presence, i.e. foregrounding information favorable to the candidate without incurring opposition, and, foregrounding information that addresses each voter’s specific issues. THE PROCESS OF ARGUMENTATION: The essay begins by reviewing the origins of the “reasonable man” assumption of audience in contested rituals in a democracy. It then applies that historic standard to modern American Presidential campaigns beginning with the oratorical period (circa 1896) and continuing through the periods dominated by radio (1925-1950) and television (1960-2004). The essay argues that the problem of presence was never resolved in these periods. RESEARCH RESULTS: The essay demonstrates how Big Data and the use of that data for psychographic analysis (in addition to the traditional demographic analysis) solves the problem of presence by allowing candidates to micro-target narratives to individuals and their specific interests. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: The essay concludes with a cautionary note about the trend toward “self-assent,” and the societal danger its poses for purging political narratives of their “contested” value to a democracy.